Association of high‐dose radiotherapy with improved survival in patients with newly diagnosed low‐grade gliomas. Issue 5 (15th November 2021) - Liu, Yanwei; Liu, Shuai; Li, Guanzhang; Li, Yanong; Chen, Li; Feng, Jin; Yang, Yong; Jiang, Tao; Qiu, Xiaoguang
Abstract : Background: The radiation dose for patients with low‐grade gliomas (LGGs) is controversial. The objective of this study was to investigate the impact of the radiation dose on survival for patients with LGGs and especially for molecularly defined subgroups. Methods: Three hundred fifty‐one patients with newly diagnosed LGGs from the multicenter Chinese Glioma Cooperative Group received postoperative radiotherapy (RT) in 2005‐2018. The RT dose, as a continuous variable, was entered into a Cox regression model using penalized spline regression to allow for a nonlinear relationship between the RT dose and overall survival (OS) or progression‐free survival (PFS). Inverse probability of treatment weighting (IPTW)–adjusted propensity scores were used to correct for potential confounders. Dose effects on survival within IDH mutation and 1p/19q codeletion defined subgroups were analyzed. Results: The risk of mortality and disease progression decreased sharply until 54 Gy. High‐dose RT (≥54 Gy) was associated with significantly better 5‐year OS (81.7% vs 64.0%; hazard ratio [HR], 0.33; P < .001) and PFS (77.4% vs 54.5%; HR, 0.46; P < .001) than low‐dose RT (<54 Gy). IPTW correction confirmed the associations (HR for OS, 0.44; P = .001; HR for PFS, 0.48; P = .003). High‐dose RT was associated with longer PFS (HR, 0.25; P = .002; HR, 0.21; P = .039) and OS (HR, 0.27; P = .006; HR, 0.07; P = .017) in IDH ‐mutant/1p/19q noncodeleted and IDH wild‐type subgroups, respectively. No significant difference in survival was observed with high‐dose RT in the IDH ‐mutant/1p/19q codeleted subgroup. Conclusions: High‐dose RT (≥54 Gy) was effective in LGGs. Patients with an IDH mutation/1p/19q noncodeletion or IDH wild‐type may need to be considered for high‐dose RT. Lay Summary: The radiotherapy dose‐response was observed in patients with low‐grade gliomas, and high‐dose radiotherapy (≥54 Gy) was associated with improved survival. Patients with an IDH mutation/1p/19q noncodeletion or wild‐type IDH may have improved survival with the administration of high‐dose radiotherapy. Abstract : High‐dose radiotherapy (≥54 Gy) is an independent protective factor for overall survival and progression‐free survival in low‐grade gliomas. Patients with an IDH mutation/1p/19q noncodeletion or IDH wild‐type benefit from high‐dose radiotherapy.